Designing, Testing and implementing a Technology-based and improved leave administration system at the UP Human resource Development Office - Lectura, Leizel; Talisayon, Serafin (Quezon City University of the Philippines Diliman, 2015)
Human Resources Development and Benefits Division (HRDBD) of the Human Resources Development Office (HRDO) aims at provision of responsive and excellent development and administration of effective human resource management service among all UP employees. Its goal is to establish realistic, systematic, efficient, and easy to follow policies and procedures.

In contrast, the HRDO have been receiving clarifications and complaints ranging from un-updated, un-reconsiled/inaccurate data from Daily Time Record, leave records, and Service Records of about 3,568 employees. These also included requests from government mandate agencies for updated service records to facilitate processing of benefits and entitlements as provided for by the GSIS, Pag-ibig and Philhealth. On top of these challenges, the eUP Project of the University of the Philippines further required "to integrate, harmonize, and interoperate information and communication technology systems and infrastructures across all constituent universities of the UP System. "9http://e.up.edu.ph/)

The HRDBD inititated database encoding using Microsoft excel and relational data manager called FoxPro formats seven (7) years ago. These manual systems of leave records' processing, updating, and validation earned recurring complaints and delivery of requests for incorrect service records, which remain up to this time. Both have served their purposes, but they have proven ineffective and inefficient. More personnel are still required to perform these tasks (e.g. posting, updating, validation, and/or encoding). HRDBD perennially missed its target with this trend.

Hence, this Designing, Testing and Implementing a technology-based and improved leave administration system at the UP Human Resource Development Office was meant as a learning paradigm of UP being a government institution to enhance its HRDO's personnel competence and operating values of efficiency and excellence; provide updated/real-time employees' leave records using quality leave processing and system through information and communication technology; and to enhance proactive management capability in the field of human resource and development.

This study: Designing, Testing and Implementing a technology-based and Improved Leave Administration System at the UP Human Resource Development Office was based on Larson, Erik W. 2011, Modern Project Management Framework on planning, implementation, and management tools.

This study has been implemented since March 2014 with HRDO's staff participation. After eight (8) months, this participatory study achieved the following objectives: 1) reviewed and evaluated the systems and procedures of HRDBD in terms of leave administration and management; 2) conducted inventory leave records 2) organized assembly line for leave records updating project; 3) establishedleave records process work flow; 4) Introduced new concepts and practices of assembly line processing and project management through orientation workshop; 5) transferred skill and knowledge in leave records, administration and management thru manualization of business processes; and 6) developed strategic leave administration and management plan to fully comply with the University and GSIS requirements for eUP-HRIS platform roll-out and processing of retirement related claims thru submission of updated Service Record.

The HRDO staff's participation was necessary in attaining these outputs:
a) Accurate and updated leave records uploaded through the HRIS platform; and
b) Immediate release of retirement claims and other related benefits from GSIS.

Overall, the study developed ten (10) HRDO staff as specialists and generalists, and enhance their operational and organizational capabilities during their participation in the Training for Leave Administrative Course For Effectiveness (LACE) conducted by the Civil Service Commission (CSC) in May 24 and 25, 2014.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Information storage and retrieval systems -- Database management; Personnel records -- Philippines; Personnel management; Database management system